2016
DOI: 10.1248/bpb.b16-00145
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intrathecal Dexmedetomidine with Morphine as Adjuvants in Cesarean Sections

Abstract: To compare the effects of intrathecal dexmedetomidine and intrathecal morphine as supplements to bupivacaine in cesarean sections under spinal anesthesia. Full-term parturients (n 120) undergoing elective cesarean sections under spinal anesthesia were randomly allocated into three groups: Group B received 10 mg bupivacaine, Group BD received 10 mg bupivacaine plus 5 µg dexmedetomidine, and Group BM received 10 mg bupivacaine plus 100 µg morphine. The onset and regression time of sensory and motor blockade, pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
58
1
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 34 publications
7
58
1
1
Order By: Relevance
“…Patients investigated in 5 trials [25, 38, 39, 44, 45] were nearly full term parturients selected for cesarean section. Five studies [22, 28, 3133] compared different doses of dexmedetomidine via subarachnoid administration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients investigated in 5 trials [25, 38, 39, 44, 45] were nearly full term parturients selected for cesarean section. Five studies [22, 28, 3133] compared different doses of dexmedetomidine via subarachnoid administration.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies [22, 28, 3133] compared different doses of dexmedetomidine via subarachnoid administration. Other control adjuvants included clonidine [40, 42, 44], fentanyl [24, 34, 39, 4345], morphine [25], midazolam [23], buprenorphine [35], and butorphanol [41]. …”
Section: Resultsmentioning
confidence: 99%
“…11,12,36) The use of dexmedetomidine as an adjuvant to bupivacaine for covering Cesarean delivery provided better intra-operative analgesia and did not affect Apgar scores or caused any noticeable side effects. 13,28) The intrathecal doses of dexmedetomidine used in our study were based on previous human studies wherein no neurotoxic effects were documented at these doses. [25][26][27][33][34][35] A limitation of this study was that a doseresponse experiment was not performed to determine the optimal dose of dexmedetomidine required for optimal suppression of shivering, but without causing any significant side effects.…”
Section: Discussionmentioning
confidence: 99%
“…11) On the contrary, many studies showed that dexmedetomidine was an effective adjuvant to intrathecal local anesthetics for prolonging the duration of analgesia for lower abdominal surgeries, lower limb surgeries and Cesarean delivery. 12,13) However, the preventive effect of intrathecal dexmedetomidine on shivering has not been evaluated.…”
mentioning
confidence: 99%
“…The lower incidence of shivering compared with our study may relate to the higher dose of dexmedetomidine (10 μg versus 5 μg). Qi et al14 compared the effects of 5 μg intrathecal dexmedetomidine with 100 μg morphine as supplements to 10 mg bupivacaine in 120 parturients undergoing elective CSs under SA. Only 7.7% of patients in the dexmedetomidine group had shivering, while 30% and 35.9% of patients in the morphine and bupivacaine groups experienced shivering, respectively.…”
Section: Discussionmentioning
confidence: 99%